2021
DOI: 10.1111/exd.14464
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 mediates itch‐associated scratching and skin barrier dysfunction in DNFB‐induced atopic dermatitis mice

Abstract: Atopic dermatitis (AD) is a common chronic inflammatory skin disease, characterized by a T helper (Th)-2 cell-dominant inflammatory infiltrate and a defective epidermal permeability barrier. 1,2 Itch (or pruritus) is the major symptom of AD and causes a negative impact on quality of life. Intense itching is an unpleasant sensation, which evokes a strong desire to scratch. Moreover, itch-induced scratching aggravates skin lesions, and a vicious itch-scratch circle and consequent skin barrier destruction are eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…This adverse effect was thought to be due to TRPV1 s role in thermoregulation [33]. Administration of a topical TRPV1 antagonist markedly reduced scratching behavior, as well as erythema and edema, in atopic dermatitis mice models by day 12 of treatment, a finding previously supported by other murine studies [34,35]. Topical TRPV1 antagonist PAC-14028 has been assessed in phase II randomized controlled trials for the treatment of mild to moderate atopic dermatitis, showing significant reduction in pruritus-related VAS scores by week 8 [36].…”
Section: Trp Vanilloid 1 (Trpv1)supporting
confidence: 62%
“…This adverse effect was thought to be due to TRPV1 s role in thermoregulation [33]. Administration of a topical TRPV1 antagonist markedly reduced scratching behavior, as well as erythema and edema, in atopic dermatitis mice models by day 12 of treatment, a finding previously supported by other murine studies [34,35]. Topical TRPV1 antagonist PAC-14028 has been assessed in phase II randomized controlled trials for the treatment of mild to moderate atopic dermatitis, showing significant reduction in pruritus-related VAS scores by week 8 [36].…”
Section: Trp Vanilloid 1 (Trpv1)supporting
confidence: 62%
“…However, the mechanism by which DNFB affects the effects of DfE remains unclear. DNFB-induced contact dermatitis may impair the skin barrier, and skin dendritic cells are more likely to capture external protein antigens through the damaged skin barrier ( 23 , 24 ). Immune modification by DNFB may be involved in this process ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even the simplest method, nail clipping, leads to a decrease in pruritus and skin-barrier defects. In a study involving mice, immunofluorescence staining and Western blot results revealed that the antipruritic effect of nail clipping or the application of a plant-based topical treatment might be explained by the suppression of IL-31 [ 31 ]. This finding alone suggests the possible role of physical stimuli as triggering factors for the secretion of IL-31, although another interesting study suggested that even intense physical activity could lead to spikes in IL-31 production [ 32 ].…”
Section: Discussionmentioning
confidence: 99%